2019
DOI: 10.3382/ps/pey438
|View full text |Cite
|
Sign up to set email alerts
|

Phytate degradation and phosphorus digestibility in broilers and turkeys fed different corn sources with or without added phytase

Abstract: The aim of the present study was to test whether different dietary corn sources and phytase supplementation affect the prececal phosphorus digestibility (pcdP) and appearance of inositol phosphates in the lower ileum of growing broiler chickens and turkeys. Two experiments were conducted, one with broiler chickens and one with turkeys. Four corn diets were provided; these were formulated to contain low P and calcium (Ca) contents and incorporated 43% of one of the four different corn sources. Diets were either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 39 publications
5
20
2
2
Order By: Relevance
“…These results indicate that the positive effect of BECP on phytate phosphorus utilisation, maybe due to liberating phosphorus from the phytic acid molecule of main components of the experimental ingredients such as maize, soybean meal and OC. These results are consistent with those reported in previous studies (Choct 2006;Attia et al 2012;Attia et al 2016;Ingelmann et al 2019).…”
Section: Calcium Phosphorus and Alkaline Phosphatasesupporting
confidence: 94%
See 1 more Smart Citation
“…These results indicate that the positive effect of BECP on phytate phosphorus utilisation, maybe due to liberating phosphorus from the phytic acid molecule of main components of the experimental ingredients such as maize, soybean meal and OC. These results are consistent with those reported in previous studies (Choct 2006;Attia et al 2012;Attia et al 2016;Ingelmann et al 2019).…”
Section: Calcium Phosphorus and Alkaline Phosphatasesupporting
confidence: 94%
“…However, the deviations in the composition of microbiota and digestibility of AA in prececal were not connected together, showing a lack of a causal relationship (Borda-Molina et al 2019). It is found that broilers exhibited a higher inositol P 6 degradation and hydrolysis of lower inositol phosphorus compared with turkeys; however, the results are affected by the source of maize fed (Ingelmann et al 2019). Hence, this study targets to investigate the impact of phytase on enhancing the use of pelleted feeds containing different concentrations of olive cake on performance, carcase traits, red blood cell characteristics, lipid metabolites and plasma calcium, phosphorus, and alkaline phosphatase of broiler chickens during 7-28 days of age.…”
Section: Introductionmentioning
confidence: 92%
“…No influence of phytase supplementation on the microbiome in turkeys were observed in the current study, and to the best of our knowledge, no such studies have been reported previously. Broilers possess a greater capacity for InsP6 degradation and hydrolysis for lower inositol phosphates compared with turkeys ( Ingelmann et al., 2019 , Olukosi et al., 2020 ), and this difference can be maximized with phytase supplementation. The differences observed between turkeys and broilers in their capacity for InsP6 hydrolysis and P digestibility may be the result of differences in small intestine maturity ( Adebiyi and Olukosi, 2015 ), endogenous P loss, pH along the GIT, passage rate ( Rodehutscord and Dieckmann, 2005 , Adebiyi and Olukosi, 2015 ), and differences in their microbiome ( Pan and Yu, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a plethora of data on the effect of phytase and xylanase supplementation in broilers ( Olukosi et al., 2007a , Olukosi et al., 2010 , Tiwari et al., 2010 , Zeller et al., 2015 ) but much less information about turkeys ( Ingelmann et al., 2018 , Ingelmann et al., 2019 ). In addition, the traditional conventional phytase levels in diets ranges between 500 and 1000 FTU/kg ( Adeola and Cowieson, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are comparatively much fewer studies on the use of phytase and/or xylanase for turkeys. And even fewer studies have directly compared the response of broilers and turkeys ( Rodehutscord and Dieckmann, 2005 , Pirgozliev et al., 2007 , Adebiyi and Olukosi, 2015a , Adebiyi and Olukosi, 2015b , Adebiyi and Olukosi, 2015c , Ingelmann et al., 2019 ) to enzymes supplementation.…”
Section: Introductionmentioning
confidence: 99%